Photopolymerization of methylmethacrylate: an inexpensive, open-source approach for the undergraduate lab - Holzman, Noah J. (University of Wisconsin--Stout. Research Services, 2015)
Light-cured polymer resins are plastics that harden after exposure to UV or visible light. The market for UV resins is expanding due to their environmental and economic benefits over conventional polymers. Using light to cure the resin allows the raw monomer to be formulated and delivered to a substrate with little to no solvents or volatile organic compounds (VOCs). Traditional industrial production of photocure products utilizes mercury vapor lamps that require a constant flow of water to prevent the light source from overheating. This research details an apparatus fabricated with opensource electronics to cure and control the polymerization process. The solid-state LED source is compact, inexpensive, customizable, and provides high-intensity (250mW/cm2 per LED) irradiation that is easily directed. These features make it readily deployable in an undergraduate or research setting for small-scale experimental use. Proof of concept is demonstrated through a photoinitiator system formulated with Michler’s ketone (4,4’-bis(dimethylaminobenzophenone) and benzophenone to achieve 97% conversion of methyl methacrylate into a high molecular weight resin. The effect of other photosensitizers and hydrogen donors on cure speed, molecular weight, yellowing and monomer conversion are reported for similar resins.
Research article with illustrations and graphs.
Keywords: polymer resins; methylmethacrylate; Methyl methacrylate; Photopolymerization